Isolation and characterization of a lignin-like polymer of the cork of Quercus suber L. (HOLZFORSCHUNG, 1996)
A lignin-like polymer was successfully extracted from the cork of Quercus suber L. using an organosolv-based technique. This material was characterized by elemental analysis, functional group analysis, nitrobenzene oxidation followed by HPLC analysis of the oxidation products, FTIR and liquid C-13 NMR. The evidence thus obtained indicated that the extracted material was composed mainly of a lignin-like polymer covalently bound to residual aliphatic structures which are not present in common lignins and which have been assigned to suberin. The latter is likely to be attached to the oxygenated side chains of the phenolic polymer but bonding through the aromatic ring can also be envisaged. No residual carbohydrates were detected. The phenolic polymer, composed mainly of guaiacyl-type units and small amounts of syringyl-type units, had a low methoxy content and a high degree of condensation. This polymer showed the presence of a fraction containing C6Cn units with n < 3 or even n < 2.